China and globalization: the insertion of the Chinese car industry in Algeria and Morocco - (:unkn) unknown (My University, 2018)
From Bandung to the present day, China's place and role in Africa have evolved considerably. Thierry Pairault shows that through the desire to integrate Chinese carmakers and manufacturers in the Algerian and Moroccan economies, the shift towards a predominant market logic in Sino-African relations is also accompanied by a gradual changeover between regions - in this case from Algeria to Morocco. Also appears a diversion of the internationalization of China. The partnerships signed by Chinese companies in the Algerian and Moroccan automobile sectors are less the manifestation of their integration than a modality of the globalization of traditional manufacturers through their Chinese partners - not to say their Chinese subsidiaries.
Keywords: African Research